Great Expectations: Past Wages and Unemployment Durations - René Böheim; Gerard Thomas Horvath; Rudolf Winter-Ebmer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
Decomposing wages into worker and firm wage components, we find that firm-fixed components (firm rents) are sizeable parts of workers' wages. If workers can only imperfectly observe the extent of firm rents in their wages, they might be mislead about the overall wage distribution. Such misperceptions may lead to unjustified high reservation wages, resulting in overly long unemployment durations. We examine the infuence of previous wages on unemployment durations for workers after exogenous lay-offs and, using Austrian administrative data, we find that younger workers are, in fact, unemployed longer if they profited from high firm rents in the past. We interpret our findings as evidence for overconfidence generated by imperfectly observed productivity.
Keywords: J3; J6; 330; Unemployment; Job Search; Overconfidence